An exploration of biosimilar TNF-alpha inhibitors uptake determinants in hospital environments in Italy, Portugal, and Spain - Barcina Lacosta, Teresa; Vulto, Arnold G.; Huys, Isabelle; Simoens, Steven (Frontiers in Medicine, 2023)
Background: The availability of biosimilar medicines in Southern European markets has allowed purchasing biologics at a lower cost for healthcare systems. However, the capacity to seize this cost-reduction opportunity in the long run depends on fostering a sustainable competitive environment for all the market players involved. Diverse policies and information campaigns have been launched in Italy, Portugal and Spain to support uptake of ‘best-value’ biologics (BVB). Despite these measures, the utilization lower-cost biologics in certain regions is low, especially when it comes to the treatment of chronic conditions. Objective: We aim to identify biosimilar uptake determinants in hospital environments in Italy, Portugal and Spain, using the class of TNF-alfa inhibitors as an example. Methods: This is a mixed-methods study based on (1) the quantitative analysis of regional uptake data for TNF-alpha inhibitor biosimilars and (2) the qualitative processing of semi-structured interviews capturing experts’ views on uptake determinants for biosimilars. Results: The organization of multi-stakeholder information campaigns supporting TNF-alfa inhibitor biosimilars use in Italy, Portugal and Spain has resulted in an increased familiarity of healthcare professionals and patients with the prescription/use of these products. However, barriers persist that impede high biosimilars uptake, especially in chronic patient populations eligible for a switch. These are: (1) the late publication of position statements on biosimilars interchangeability by regulatory health authorities; (2) the vague positioning of (national/regional) health authorities on best switching practices (including multiple biosimilar-to-biosimilar switches); (3) the existence of policy frameworks that do not necessarily support the initiation of switching protocols; (4) the establishment of sometimes inefficient purchasing procedures that limit biosimilars potential to compete for market shares. Diverse approaches taken regionally to address these barriers have contributed to heterogeneous TNF-alfa inhibitor biosimilars uptake across Southern Europe. Conclusion: Our research signaled the limited reach of biosimilar policies implemented locally, if not supported by a national policy framework. This study highlights the need for the coordinated implementation of policy measures fostering biosimilars use at the national/regional level in Italy, Portugal and Spain. These measures should account for the particularities of off-patent biologic and biosimilar markets and should jointly address supply- and demand-side challenges.